The 10th kingdom - Carson, David, director; Wise, Herbert; Williams-Paisley, Kimberly, 1971-; Cohen, Scott, 1961-; Larroquette, John (Minneapolis, MN : Mill Creek Entertainment, 2013)
A janitor and his beautiful young daughter are taken to a magical land through a portal to help Prince Wendell, who has been turned into a dog by the evil queen, regain his throne.
Features: making-of featurette.
Kimberly Williams-Paisley, Scott Cohen, John Larroquette, Dianne Wiest, Daniel Lapaine.
Originally broadcast on television in 2000.
TV rating: TV-PG.
DVDs, Dolby digital 2.0.
Keywords: Imaginary places -- Drama; Magic -- Drama; Good and evil -- Drama; Action and adventure television programs; Romance television programs; Television mini-series.; Fiction television programs; Fantasy television programs